Pelatihan “Remaja Bijak” terhadap Kecenderungan Perilaku Prososial Remaja - Maria Theresia; Esti Hayu Purnamaningsih (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2019)
Behavioral problems in adolescents at school become a phenomenon that is increasingly seen nowadays. Prosocial behavior is important for adolescents to carry out their social functions well. One important aspect that influences the tendency of prosocial behavior is emotion. The study’s objective was assessing the role of "Remaja Bijak" in improving adolescent emotional intelligence. An increase in adolescent emotional intelligence was expected to influence the increasing tendency of adolescent prosocial behavior. The training was given to adolescents aged 16-17 years. The results showed that there was no effect on "Remaja Bijak" training on the tendency of adolescent prosocial behavior. Improvements to the contents of the module can be considered in future studies